Pesmi v ilegalnih goriških publikacijah v obdobju med vojnama - Toroš, Ana (Jezik in slovstvo, 2017)
The article discusses the poems published in illegal publications in the Goriška region between the First and Second World Wars; specifically, in the journals Soča, Tihe besede, Pisanice, Gmajna, Brinjevke and Tavžentroža. While most of the poems were written by Lado Piščanc, Alojz Kocjančič, Ljubka Šorli and Milko Matičetov, the publications also contain poems by Srečko Kosovel, Stanko Vuk and France Svet. The poems speak about the oppression of Slovenian identity in Venezia Giulia. A religious component is also clearly present, as most of the authors attended religious schools in the town of Gorica. In the same period, poems referring to Trieste were also published in illegal publications present in the Trieste region. These poems also deal with the oppression of Slovenian identity and thus reflect similar literary patterns to describe the relationships between domestic and foreign cultures. The poetry found in the illegal publications in Goriška represents a particular and as yet relatively unknown chapter of Slovenian literary history of special importance, as it also comprises certain poems by Ljubka Šorli and Milko Matičetov that are not published elsewhere.
Keywords: Piščanc, Lado, 1914-1944; Matičetov, Milko, 1919-2014; Kocjančič, Alojz, 1913-1991; Šorli, Ljubka, 1910-1993; poezija; ilegalne publikacije; Goriška